Science for all - myth or reality?: a research project - Valiathazhel, James Daniel (Rhodes University, Faculty of Education, Department of Education, 2002)
Abstract: Transformation at a historically disadvantaged technikon in South Africa : a research project: South Africa is in the seventh year of democracy. During the first term of office, the ANC government proposed radical shift from the system(s) of education that was/were in existence in this country. A change in the education system in South Africa was inevitable. The ANC government have realised the need and proposed plans for a change in the education system in this country. We might be able to overcome the inequalities of the past and have an education system relevant for all South Africans that promote an equal opportunity for success as envisaged by Outcomes Based Education (OBE). This research project, using a qualitative case study methodology, reports on the readiness of Border Technikon in implementing Outcomes Based Education (OBE) as a teaching/lecturing strategy. Since 1998 Border Technikon organised a series of staff training workshops to empower the academic staff in Outcomes Based Education. A preliminary study on the topic was conducted during 1999, in which questionnaires (to 16 academic staff) and semi-structured interviews (with three academic staff) were used to collect data. During 2000, when the second and final round of this study was conducted semistructured interviews were employed with 4 staff members to gather data. Literature review and document analysis was also part of the research. The analysis of data indicated that the very nature of most of the Technikon Programmes demands an OBE approach in teaching/lecturing and hence OBE based teaching/lecturing is largely practised at Border Technikon. However a few areas of concerns were identified. Some of these concerns were: (i) Technikon employed academic staff (from industry, etc...) with no professional qualification in teaching and it was difficult to provide OBE training to such people and (ii) lack of sufficient support from the Technikon Management might be a cause for the poor attendance of academic staff during the training programme. Another aspect emerged from the data analysis was that all academic staff participated in this study expressed the need for further training in OBE and related topics. Abstract: Science for all - myth or reality?: Different educational projects around the world have made Scientific Literacy a world-wide concern. This study through a literature review shows that Scientific Literacy is a term that has many definitions and interpretations. This literature review reveals that, in the present system Science for All is a myth for various reasons. Governments around the world in general, and South Africa in particular, are in the process of introducing different projects such as the Year of Science and Technology (YEAST), science week and science exhibitions for the purpose of popularising science and technology. The Department of Education in Thailand has modified its education system to accommodate Science for All. In this literature review among other issues the status quo in South African science education and the Thailand model were examined. A few recommendations to achieve Science for All are also included in this project. Abstract: Developing and evaluating the use of learning material in science - a constructivist approach towards learning Newton's laws : a research project: The Government of National Unity in 1994 introduced a new educational policy for South Africa. This represented a shift in paradigm from a transmission mode of teaching and learning to a learner-centred education. The shift marks a transformation from a content-based curriculum to an Outcomes Based Education (OBE). Various authors found that different sections in the Physical Science syllabus in South Africa are often misunderstood by students for different reasons. One of the reasons was that students had their own ideas about laws of nature and these (mis)conceptions were resistant to change. From the literature and from the author's personal experience it was found that Bodies in Motion is a topic that is difficult to conceptualise by students of different age groups. The challenge facing educators is how to tackle this issue. In this research project a diagnostic test is developed and used to identify the topics where students have conceptual problems. To address these problem areas further, concept sheets/work sheets where developed and implemented. The different challenges and tasks given in the work sheets/learning material are organised in such a way as to make the students aware of their own ideas about Bodies in Motion in general and the key-concepts in particular and also to make them aware of the ideas of their peers (group members). It was also aimed at offering the learners the scientific alternative to their own beliefs. At the end, it was discovered that, even though the general understanding of the learners has improved in this topic (namely, Bodies in Motion), their original beliefs were largely unaffected. It is the hope of the researcher that the project would be the basis for further research on the development of learning material in science.
Keywords: Science -- Study and teaching -- South Africa; Motion -- Study and teaching -- South Africa; Physics -- Study and teaching -- South Africa; Competency-based education -- South Africa; Educational change -- South Africa; Technical institutes -- South Africa; Technical education -- South Africa